Robert Kilwardby's Commentary on the Ethics of Aristotle
1 online resource.
Keywords: This work contains the Latin text of an early medieval commentary on the first three books of Aristotle's Ethics . The commentary appears here in print for the first time, supported by an introduction considering the significance of the work and the attribution of it to the Dominican author, Robert Kilwardby (c. 1215-1279). Celano argues that the commentary represents an early phase in the reception of Aristotle's Ethics in the thirteenth century, and that Kilwardby demonstrates a perceptive understanding of the meaning of Aristotle's moral philosophy, showing its importance for the curriculum in the Arts Faculties of universities in the Middle Ages.